Numerical Simulation of Single Tooth Rock Breaking Mechanism Under High Temperature Environment - Ye, Xian; Gao, Qingchun; Zhang, Xuan; Liu, Shengxu (International Journal of Natural Resources and Environmental Studies, 2025)
In high-temperature geothermal drilling, due to the high hardness and strong abrasiveness of the formation rock, and the rock drillability is significantly reduced in high-temperature environments, the working efficiency of traditional PDC drill bits decreases, and it is necessary to further explore the rock-breaking mechanism under high-temperature conditions. To this end, the research systematically examined the influence of high temperature on the single-tooth rock breaking process. Through numerical simulation, the effect of temperature on the single-tooth cutting process was explored. The results show that as the temperature increases, the rock damage first decreases and then increases. The damage is minimal at 200°C. The weakened rock strength at high temperature helps to improve the rock breaking efficiency. The Cpress stress of the tooth edge increases from the lowest point on both sides and is symmetrically distributed. The contact area is about 50°. The stress is the highest and fluctuates the most at 200°C, which is easy to cause uneven wear and is not conducive to the life of the cutting teeth. If the temperature continues to increase, the stress distribution will tend to Uniform; the increase in rake angle leads to the expansion of the high-temperature zone on the tooth surface, intensification of stress and fluctuations, and aggravates unbalanced wear; the increase in penetration increases the Cpress stress, expands the contact area, and intensifies stress fluctuations, which also affects the life of the cutting teeth. Tooth profile comparison shows that 3D tooth profiles such as roof teeth and Mercedes-Benz teeth have the advantages of large rock damage, high rock breaking efficiency, and small stress fluctuations in high-temperature and high-abrasive formations, and are more suitable for high-temperature geothermal drilling. The research results provide key theoretical support and parameter basis for the optimal design of high-temperature geothermal drill bits.